New specific migraine prevention: monoclonal antibodies against calcitonin gene-related peptide and its receptor - Ryliškienė , K.; Jatužis , D.; Vaitkus , A. (Neurologijos seminarai, 2019)
Migraine is a long-lasting neurological disorder with significant negative impact not only on the patient’s life, but also on society. For many years, preventive treatment of migraine included drugs developed for diseases other than migraine such as hypertension, depression, and epilepsy. During the last decade, blocking calcitonin gene-related peptide (CGRP) has emerged as a possible mechanism for preventing migraine attacks, and monoclonal antibodies against CGRP and its receptor for the specific migraine prophylaxis have been developed. Results of clinical trials, safety and tolerability of the new class of drugs as well as guidelines for their use for the prevention of migraine are presented in this review article.